THU0108 11. RHEUMATOID ARTHRITIS – PROGNOSIS, PREDICTORS AND OUTCOME CONCORDANCE BETWEEN PHYSICIAN AND PATIENT ASSESSMENT OF DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS USING DISEASE ACTIVITY SCORE. (June 2019) - Ziade, Nelly; Daher, Amani; Zorkany, Bassel; Emadi, Samar Al; Halabi, Hussein; Jbara, Mohammad Abu; Kibbi, Lina; Saad, Sahar; Mashaleh, Manal; Merheb, Georges; Alam, Elie; Mroue', Kamel; et al.
Abstract : Background: Involving patients with rheumatoid arthritis (RA) in the assessment of their disease may increase adherence to treatment, improve disease outcomes and reduce consultation time. Objectives: To evaluate the concordance between physician and patient assessment of disease activity in RA using Disease Activity Score (DAS-28). Methods: During the routine consultation, patients were briefed about DAS-28 by their rheumatologist. Using a standard DAS-28 mannequin, physicians, patients and nurses reported the number of tender and swollen joint, inflammatory markers and global health on a 0-10 Likert scale. DAS-28, Clinical Disease Activity Index (CDAI) and Simple Disease Activity Index (SDAI) were calculated blindly by each participant. Agreement between physician- and patient-DAS categories was calculated using weighted kappa (WK) for category comparison. Concordance between physician- and patient-DAS was estimated using the Bland-Altman method. Predictive factors of positive concordance between physician and patient-DAS were identified using logistic regression. Results: Four hundred and twenty patients from 7 Middle-Eastern countries were included, with a mean age of 49 years (SD 12), 84% of females, disease duration of 11 years (SD 8). Mean physician-DAS-28 was 4.03 (SD 1.51). 65% had positive rheumatoid factor, 56% had positive ACPA, 30% had erosive disease and 34% were on biotherapy. Agreement between physician- and patient-DAS categories was 89%, WK was 0.84. WK were 0.80 for DAS physician-nurse, 0.79 for DAS patient-nurse, 0.83 for CDAI physician-patient and 0.88 for SDAI physician-patient agreements respectively. All activity measures were higher in patients compared to physicians, except for the swollen joints count. The mean difference between physician- and patient-DAS was -0.09 [95% CI -0.14; -0.04] and was smaller in patients in remission (Figure 1 : Bland Altman plot). Concordance was statistically associated with CRP and patient SDAI. Conclusion: Concordance between patient and physician assessment of disease activity in RA was excellent and was higher using SDAI followed closely by DAS-28 and CDAI. Self-assessment of disease activity should be decided according to the physician's clinical judgment. References: [1] Gossec L, et al. Arthritis Rheumatol 2016; 68 (suppl 10). [2] Smolen J, et al. Arthritis Research & Therapy (2016) 18:114. [3] Studenic Pet al. Arthritis Rheumatol. 2012;64(9):2814–23. The physician-patient DAS-mean is plotted on the X-axis. The physician-patient DAS-difference is plotted on the Y-Axis. The horizontal black line corresponds to the mean DAS difference (-0.09 [95% CI -0.14; -0.04]). The horizontal blue lines correspond to +/-1.96 SD. The vertical red line corresponds to the DAS-28 cut-off for remission (2.6). Disclosure of Interests: None declared